Hedonic bull pricing models: estimating the value of traits of bulls sold following performance testing - Stephens, Daren (Kansas State University, 2015)
Selection of a herd sire has always been of paramount importance given the initial financial investment and their contribution and effect on the genetic make-up of a beef herd. Data was collected from the nation’s longest consecutively run bull test conducted at the University Farm of Oklahoma Panhandle State University (OPSU). The Bull Test and Bull Sale data utilized were collected from 2008-2013. Performance data was collected over a 112 day test period with data collection occurring at 28 day intervals. The top seventy bulls from each year’s test were selected based upon a performance index of ½ ADG and ½ weight per day of age (WDA), and a semen quality and motility score of excellent and sold at auction. Angus bulls were the focus of the study as they represented the vast majority of individuals sold. Three hedonic pricing models were created to try to determine what attributes buyers at the OPSU bull test sale were placing emphasis on. The initial hedonic model contained production data that included BW, ADG, WDA, Julian age, final test weight ultrasound data, and a dummy variable for sale year. The second model utilized all production data and added genetic variables in the form of production EPDs (Calving Ease Direct (CED), BW, Weaning Weight and Yearling Weight) and maternal EPDs (Calving Ease Maternal, Maternal Milk). The third model included the variables from the first and second models with the inclusion of carcass EPDs (Marbling, Ribeye Area (REA) and FAT). Year was significant in all three models however there was less of an effect on price as more variables were included. In model one, the production facts that were of significance were: ADG (P<0.01), BW (P<0.01) and final test weight (P<0.01). In the second model, ADG, BW and final test weight retained their significance at the P<0.01 level. The only production EPD that was significant (P<0.05) was CED. In the third model, years, ADG and BW were still significant (P<0.01). Final test weight (P=0.70) and CED (P = 0.132) had substantial changes. The carcass EPD ribeye area had a P value of 0.057. Producers who are placing bulls on test can utilize the given information to assist with their selection. It cannot go unsaid that while single trait selection can be very detrimental; ADG was significant across all models. The study indicates that performance and growth are of utmost importance to buyers, followed by birth weight consideration.
Keywords: Hedonics; Bulls; Pricing; Performance; Economics; EPD; Agriculture, General (0473); Animal Sciences (0475); Education, Agricultural (0517)